The philosophy of generative linguistics - Ludlow, Peter, 1957- (Oxford : Oxford University Press, 2011)
Peter Ludlow presents this work on the philosophy of generative linguistics. He explains the motivation of the generative framework, describes its mechanisms, and addresses issues of broad philosophical interest, for instance the ontology of linguistics, the nature of data, language/world relations, and best theory criteria.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (viewed on May 11, 2011).
Keywords: Generative grammar -- Philosophy